\[ \large { \pi }^{ 2 }=\frac { 128 }{ 9 } -128\displaystyle\sum _{ n=1 }^{ \infty }{ \frac { n+1 }{ (2n+1)(2n-1)(2n+3)^{ 2 } } } \]

I was playing with the expansion of \(t^2\sqrt{1-t^2}\) and I came to the series above, can you prove it?

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestHere is a quick method.

Using partial fractions, we have,

\(\displaystyle \sum_{n=0}^{\infty} \dfrac{n+1}{(2n+1)(2n-1)(2n+3)} = \sum_{n=0}^{\infty} \left[-\dfrac{1}{16(2 n+1)} + \dfrac{1}{64(2 n+3)} - \dfrac{1}{16 (2 n+3)^2} + \dfrac{3}{64 (2 n-1)} \right] \)

By Regularization, we have,

\(\displaystyle = \dfrac{1}{32} \psi\left(\dfrac{1}{2}\right) - \dfrac{1}{128} \psi\left(\dfrac{3}{2}\right) -\dfrac{1}{64} \psi^{(1)} \left(\dfrac{3}{2}\right) + \dfrac{3}{2} \psi \left(-\dfrac{1}{2}\right) \)

Note that,

\(\displaystyle \psi \left(\dfrac{1}{2}\right) = -\gamma - \ln 4\)

\(\displaystyle \psi \left( \dfrac{3}{2} \right) = 2 - \gamma - \ln 4\)

\(\displaystyle \psi^{(1)} \left(\dfrac{3}{2}\right) = \dfrac{\pi ^2}{2} - 4 \)

\(\displaystyle \psi \left(-\dfrac{1}{2} \right) = 2 - \gamma - \ln 4\)

\(\displaystyle \implies \sum_{n=0}^{\infty} \dfrac{n+1}{(2n+1)(2n-1)(2n+3)} = - \dfrac{\pi^2}{128}\)

\(\displaystyle \implies \sum_{n=1}^{\infty} \dfrac{n+1}{(2n+1)(2n-1)(2n+3)} = \dfrac{1}{9} - \dfrac{\pi^2}{128} \)

Log in to reply

Could someone please explain what \(\gamma\) is? I've seen it used in a lot of places without a definition. Is it a variable to represent infinity? Because the series \(\displaystyle\sum_{n=0}^{\infty} \frac{-1}{16(2n+1)}\) definitely diverges, for instance

Log in to reply

@Ariel Gershon Note that the individual sums are not equal to the digamma values I wrote. They are assigned that value, i.e, if the individual diverging sums appear along with some other diverging series such that their value (taken together) is converging, then we can evaluate them by their assigned values. It is similar to assigning a value of \(-\dfrac{1}{12}\) to \(\zeta(-1)\), which in fact, diverges. \(\gamma\) is the Euler - Mascheroni constant which is equal to \(- \psi (1)\).

Log in to reply

It is euler-mascheroni constant.

Log in to reply

Log in to reply

Yeah even I did it the same way. I had posted a similar problem which uses digamma.

Log in to reply

nice proof!

Log in to reply

@Hummus a How can we solve it using series expansion? (As you have stated)

Log in to reply

Log in to reply

Log in to reply

Here is a way to solve it without digamma functions:

We start out with the partial fraction expansion: \[128\sum_{n=1}^{\infty} \frac{n+1}{(2n+1)(2n-1)(2n+3)^2} = \sum_{n=1}^{\infty} \left(-\frac{8}{2n+1} + \frac{6}{2n-1} + \frac{2}{2n+3} - \frac{8}{(2n+3)^2}\right)\]

We can split this into three different sums: \[= \sum_{n=1}^{\infty} \left(\frac{8}{2n-1}-\frac{8}{2n+1}\right) - \sum_{n=1}^{\infty}\left(\frac{2}{2n-1} - \frac{2}{2n+3}\right) - \sum_{n=1}^{\infty}\frac{8}{(2n+3)^2}\]

The first sum is a telescoping sum: \[ \left(\frac{8}{1}- \color{red}{\frac{8}{3}}\right) + \left(\color{red}{\frac{8}{3}}-\color{green}{\frac{8}{5}}\right) + \left(\color{green}{\frac{8}{5}}-\frac{8}{7}\right) + ...\] Every term gets cancelled except the first one. Therefore the first sum is \(8\).

The second one is also a telescoping sum, but it's a little more tricky. The cancellation starts happening at the third term, so the result is the sum of the positive parts of the first two terms: \[\left(\frac{2}{1} - \color{red}{\frac{2}{5}}\right) + \left(\frac{2}{3} - \color{orange}{\frac{2}{7}}\right) + \left(\color{red}{\frac{2}{5}} - \color{green}{\frac{2}{9}}\right) + \left(\color{orange}{\frac{2}{7}} - \frac{2}{11}\right) + \left(\color{green}{\frac{2}{9}} - \frac{2}{13}\right) + ...\] Only the terms \(\frac{2}{1}+\frac{2}{3}\) don't get cancelled out. Therefore the value of the second sum is \(\frac{8}{3}\).

Now let's find the last sum, using the fact that \(\sum_{k=1}^{\infty} \frac{1}{k^2} = \frac{\pi^2}{6}\): \[\sum_{n=1}^{\infty}\frac{8}{(2n+3)^2} = 8\left(\frac{1}{5^2} + \frac{1}{7^2} + \frac{1}{9^2} + \frac{1}{11^2} + ...\right)\]\[= 8\left[\left(\frac{1}{1^2} + \frac{1}{2^2} + \frac{1}{3^2} + \frac{1}{4^2} + ...\right) - \left(\frac{1}{2^2} + \frac{1}{4^2} + \frac{1}{6^2} + \frac{1}{8^2} + ...\right) - \frac{1}{1^2} - \frac{1}{3^2}\right]\]\[ = 8\left(\sum_{k=1}^{\infty} \frac{1}{k^2} - \frac{1}{2^2} \sum_{k=1}^{\infty}\frac{1}{k^2} - 1 - \frac{1}{9}\right)\]\[= 8\left(\frac{\pi^2}{6} - \frac{\pi^2}{4*6} - \frac{10}{9}\right) = \pi^2 - \frac{80}{9}\]

Therefore, the total is: \[\frac{128}{9} - \left[\sum_{n=1}^{\infty}\left(\frac{8}{2n-1}-\frac{8}{2n+1}\right) - \sum_{n=1}^{\infty}\left(\frac{2}{2n-1} - \frac{2}{2n+3}\right) - \sum_{n=1}^{\infty}\frac{8}{(2n+3)^2}\right]\]\[ = \frac{128}{9} - \left[8 - \frac{8}{3} - \left(\pi^2 - \frac{80}{9}\right)\right] = \pi^2 \]

QEDLog in to reply

Careful there, you need to justify why you can split an infinite sum into two or more infinite sums. Hint: Prove that all these infinite sums are absolutely convergent.

Otherwise, neat solution! =D =D

Log in to reply

Good point. I did prove that each of the 3 sums converge, and since all the terms in each one are positive, they are absolutely convergent. :)

Log in to reply

i totally agree

Log in to reply